2016
DOI: 10.1371/journal.pone.0148158
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Characterization of the Recently Emerged Poultry Pathogen Ornithobacterium rhinotracheale by Multilocus Sequence Typing

Abstract: Ornithobacterium rhinotracheale (ORT) is an economically important bacterial pathogen of turkeys and chickens worldwide. Since its first detection, a variety of typing methods have been used to gain basic knowledge about the bacterial population structure, an issue that still needs to be addressed. Serological characterization revealed at least 18 different serotypes (A-R) with ORT of serotype A to be predominate among poultry. This study aimed to establish a multilocus sequence typing (MLST) scheme for ORT th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 34 publications
2
43
0
1
Order By: Relevance
“…All bacterial hosts of the chromosomal genes in this group, both the representative genes and the members of the families, belonged to the phylum Bacteroidetes. Two of the families in this group consisted of genes located in pathogens, where G29 in family 22 was found on the chromosome of an isolate from the poultry pathogen Ornithobacterium rhinotracheale [37] and G04 in family 4 was present on a plasmid harbored by an isolate of the opportunistic pathogen Myroides odoratimimus [38]. …”
Section: Resultsmentioning
confidence: 99%
“…All bacterial hosts of the chromosomal genes in this group, both the representative genes and the members of the families, belonged to the phylum Bacteroidetes. Two of the families in this group consisted of genes located in pathogens, where G29 in family 22 was found on the chromosome of an isolate from the poultry pathogen Ornithobacterium rhinotracheale [37] and G04 in family 4 was present on a plasmid harbored by an isolate of the opportunistic pathogen Myroides odoratimimus [38]. …”
Section: Resultsmentioning
confidence: 99%
“…Several studies (Amonsin et al, 1997;Thieme et al, 2016) have proposed that the limited heterogeneity found among isolates can be explained by the fact that the O. rhinotracheale isolates recovered over large geographic areas and long time periods are a small group of closely related clones. Although the number of isolates and the geographic areas from which the isolates were obtained were limited, both the ERIC-PCR and RAPD analyses presented here support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we were able to discriminate O. rhinotracheale isolates with both ERIC-PCR and RAPD assays using different primers, at least to a certain level. Although a multilocus sequence typing method and database have recently been established (Thieme et al, 2016), repetitive extragenic palindromic PCR and RAPD assays remain relatively cost-efficient, rapid, sensitive, and specific typing methods, and may therefore be useful in epidemiological studies of O. rhinotracheale outbreaks. In this study, ERIC-PCR proved the most useful technique for detecting intraspecies genetic diversity in O. rhinotracheale isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene was found to demonstrate identity ranging from 85.1% to 100%. This sequencing protocol can identify and differentiate Ornithobacterium species [72]. Genetic characterization of ORT isolates can also be performed by modified PCR techniques, such as enterobacterial repetitive intergenic consensus-PCR (ERIC-PCR), repetitive element palindromic PCR (REP-PCR), random amplified polymorphic DNA-PCR (RAPD-PCR), and MLST [56].…”
Section: Genetic Relatednessmentioning
confidence: 99%